Students’ perceptions of online assessment, feedback practices, and challenges - Sama'a Al Hashimi; Yazan Alamarat; Yasmina Zaki (Institute of Advanced Engineering and Science, 2022)
Online learning has become an integral part of today’s educational system, especially after the COVID-19 pandemic. In art and design classrooms, which usually require face-to-face critique as part of a cycle of action and reflection, students may face challenges with the rapid transition to online assessment and feedback approaches. Consequently, it is curial to investigate these challenges as well as students’ perceptions towards the online assessment and feedback methods that they have experienced. This student-oriented study investigated art and design students’ preferences, concerns, and challenges with online assessment and feedback strategies. Moreover, it explored the most effective online assessment and feedback tools and applications for art and design courses. The research adopted a quantitative method by conducting a questionnaire with 104 art and design students of a university in Bahrain and a university in Jordan. Based on the findings, the study seeks to ultimately provide art and design educators with insights and recommendations for the most effective art and design assessment practices.